Ovarian tissue cryopreservation by vitrification: The first Vietnam experience - Lan, Nguyen TT; Tri, Nguyen C; Diem, Nguyen TN; Thu, Tran B; Kiet, Truong D; Vinh, Dang Q; Tien, Nguyen V; Tuong, Ho M (Vietnam Journal of Biotechnology, 2024)
Ovarian Tissue Cryopreservation (OTC) is a promising technique for reproductive preservation in women with cancer. Although this technique has been successfully applied in many Invitro Fertilization (IVF) centers worldwide, OTC has not been recently developed in Vietnam, and there are no publications of OTC. The study of OTC by vitrification at IVFMD, My Duc Hospital, was conducted from 2018 to 2023 with trial registration number NCT04666376. Ovarian tissues from each patient were divided into 3 groups: group 1, which consisted on fresh tissues as a control group; group 2, which consisted of vitrified tissues using the Ova Kit Type M (Kitazato, Japan); and group 3, which consisted of vitrified tissues using IVFMD medium. The findings showed that the rates of viable follicles and follicles with both healthy oocytes and CGs in groups 2 and 3 were significantly lower than in group 1, at [80.3% in group 1, 70% in group 2, and 65% in group 3] and [71.3% in group 1, 59.4% in group 2, and 58.3% in group 3] respectively (P < 0.05). The results aligned with previous findings due to the negative effects of cryopreservation. Moreover, it was illustrated that there was no change in the quality of tissue between the commercial medium and IVFMD’s medium in OTC.